Universal design and empathic design for engineers - Dorota Kamińska; Grzegorz Zwoliński; Luis Pinto-Coelho; Rui Raposo (Nofer Institute of Occupational Medicine, 2023)
This article explores the relevance of universal design and empathic design in education. The universal design focuses on creating accessible and usable products, environments, and systems for individuals with diverse abilities. Empathy, on the other hand, involves understanding and sharing the feelings of others, encompassing cognitive, emotional, and compassionate empathy. The article investigates the application of empathy in design, particularly its importance for engineers. Teaching empathy to engineers is emphasized as a crucial aspect. By developing empathic skills, engineers gain a deeper understanding of user needs and perspectives, leading to more inclusive and user-centered design solutions. Effective communication techniques such as asking open-ended questions, active listening, observation, and perspective-taking are explored to enhance empathy in communication. The article also explores methods for measuring empathy, thus enabling engineers to assess the effectiveness of their empathic design approaches. The challenges facing students, teachers, and university authorities in implementing such courses are also bulleted. Med Pr. 2023;74(3):211-25